2002
DOI: 10.1097/00001888-200207000-00037
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Residents as Learners and Teachers of Evidence-based Medicine

Abstract: Skills are best acquired in an environment which promotes active learning supervised by experts and provides frequent opportunities to practice the skills. Residents have responded positively to our curriculum and have presented high-quality conferences. Evaluation data being collected now (resident self-assessments and evaluations of the experience, faculty assessments of presentations, pre- and post-second year written assessments of knowledge) will inform us if the desired outcomes are being attained. Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Evidence-based medicine has been implemented in some surgical residency programs and has been found to be beneficial in many cases (Bazarian et al 1999, Edwards et al 2002, Bhandari et al 2003b, Grant 2005, Nicholson and Shieh 2005 (Hurwitz et al 2000). With the increase in healthcare costs due to new techniques and an aging population, it may be necessary to move towards using interventions that are based on high-quality clinical research with patient-important outcomes and demonstrated cost-effectiveness .…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence-based medicine has been implemented in some surgical residency programs and has been found to be beneficial in many cases (Bazarian et al 1999, Edwards et al 2002, Bhandari et al 2003b, Grant 2005, Nicholson and Shieh 2005 (Hurwitz et al 2000). With the increase in healthcare costs due to new techniques and an aging population, it may be necessary to move towards using interventions that are based on high-quality clinical research with patient-important outcomes and demonstrated cost-effectiveness .…”
Section: Overviewmentioning
confidence: 99%
“…While this is partially correct, several reports do suggest that EBM education instills greater satisfaction and good retention skills in trainees (Nicholson and Shieh 2005). Also, practicing evidence-based medicine is perceived to be helpful in structuring daily clinical decision making (Kellum et al 2000, Edwards et al 2002, Korenstein et al 2002, Ismach 2004, Fingerhut et al 2005, Kuhn et al 2005, Nicholson and Shieh 2005, Petrisor and Bhandari 2006. While it may be difficult to ascertain the effectiveness of evidencebased medicine as a whole, it is not so difficult to see how some of the parts that make up evidencebased medicine play a role in patient care.…”
Section: Misconception 6: Ebm Is Not Evidence-basedmentioning
confidence: 99%
“…1,2 In today's training environment, duty hour restrictions have shortened time available for conference attendance, and conference time must be used wisely to justify removing residents from clinical duties in their shortened workday. Many programs are considering new conference structures to maximize learning in available time.…”
Section: Introductionmentioning
confidence: 99%
“…In medical undergraduate studies student tutors were successfully used in problem-oriented teaching of paediatrics [20] and graduate tutors in the core paediatrics curriculum [12]. Edwards et al [3] report on the successful use of graduate tutors in paediatric post-graduate specialisation in evidence-based medicine. The paediatrics clinic of the University of Tübingen introduced the concept of student tutoring in the paediatrics block work placement some years ago.…”
Section: Introductionmentioning
confidence: 99%